Unveiling frequency-dependent dielectric behavior of cellulose-based polymer electrolyte at various temperature and salt concentration - Qolby Sabrina; Titik Lestariningsih; Adam Febriyanto Nugraha; Sotya Astutiningsih; Mochamad Chalid; Christin Rina Ratri (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Dielectric behavior of cellulose-based polymer electrolyte was studied at various temperature and salt concentration. A polymer electrolyte membrane based on cellulose acetate (CA) as the polymer host and LiClO4 as the dopant salt was fabricated using the solution casting technique. The dopant salt concentration was varied as 0.3, 0.5, 0.67, and 1M. Dielectric relaxation spectroscopy characterization were performed using potentiostat at frequency ranging from 0.1 Hz to 1 MHz. Measurements were performed by sandwiching the membrane between stainless steel plates. The ionic conductivity was then calculated based on the Cole–Cole plot obtained from the impedance measurement. It was found that sample 1 M had the highest ionic conductivity at high frequencies. However, the frequency-dependent conductance plot showed that the ionic conductivity of the 1 M sample significantly decreased at low frequencies, i.e. from 3.41×10-5 S/cm at 1 MHz to 1.9×10-8 S/cm at 0.1 Hz. Other samples did not experience this phenomenon, including those with a Celgard© commercial membrane to represent commercial Li-ion batteries. This is caused by excess charge accumulation, leading to a high concentration of immobile charge carriers, which reduces the available free volume surrounding the polymer chain. This resulted in a significant decrease in ionic conductivity at low frequencies. Temperature variation was also performed on the conductivity measurement at 30-70 °C. Temperature variation showed more predictable behavior, where increasing the temperature activated charge carriers and enhanced ionic conductivity, from 1.81×10-5 S/cm at room temperature to 9.04×10-5 at 70°C. Sweeping across the frequency range results in a consistent sequence of ionic conductivities among the samples at various temperatures. This work is beneficial for evaluating a biomass-based polymer electrolyte complex in a Li-ion battery environment. Feasibility studies can be performed at various concentrations and temperatures to determine the optimal level of dopant salt input across a broad frequency range.